2016
DOI: 10.1038/jhh.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid is an independent predictor for developing prehypertension: a population-based prospective cohort study

Abstract: Although the prevalence of prehypertension is rapidly increasing in China, the medical community has paid little attention to its prevention. Prior studies have demonstrated that uric acid directly contributes to vascular remodelling and endothelial dysfunction. However, few prospective studies have assessed the relationship between serum uric acid and prehypertension. We therefore designed a larger-scale cohort study to examine whether uric acid level is a predictive factor for developing prehypertension in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“… 47 determined that no association existed between elevated serum UA level and prehypertension; this might be because of higher background rate of prehypertension with increasing age that would contribute to a reduction in the odd ratios for serum UA. Recently, a prospective cohort study demonstrates that serum UA is an independent predictor for developing prehypertension 48 . In addition, Soletsky et al .…”
Section: Discussionmentioning
confidence: 99%
“… 47 determined that no association existed between elevated serum UA level and prehypertension; this might be because of higher background rate of prehypertension with increasing age that would contribute to a reduction in the odd ratios for serum UA. Recently, a prospective cohort study demonstrates that serum UA is an independent predictor for developing prehypertension 48 . In addition, Soletsky et al .…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study of 15,143 subjects identified a similar risk for incident prehypertension with a 9% increased risk for those with SUA levels in the fourth quintile of the population, and 17% risk for those with levels in the fifth quintile, compared with those in the bottom quintile. 119 Cicero and colleagues selected 619 individuals from the Brisighella Heart Study and found a significant incremental increase in risk of hypertension and metabolic syndrome, along with an increase of carotid intima media thickness (CIMT), in those progressing from the second to fourth quartile of SUA measurement (from 23% to 56.3% for hypertension prevalence). 120 These were otherwise healthy individuals (mostly adults) without known cardiovascular disease.…”
Section: Epidemiological Studies Demonstrating Associationmentioning
confidence: 99%
“…Hyperuricemia (elevated serum uric acid) has emerged as one of the strongest risk factors for the development of prehypertension 1 , primary hypertension 2, 3 , and resistant hypertension 4 . Experimentally raising uric acid in rats also causes hypertension.…”
Section: Introductionmentioning
confidence: 99%